Optimasi Produksi Padi di Lahan Rawa Pasang Surut - TITA RUSTIATI; ADE RUSKANDAR (Fakultas Pertanian Universitas Udayana, 2014)
Optimization of Rice Production in Tidal Swampland.The study aimed to obtain the optimumtechnology of tidal swamplands for rice farming sustainability, acquired some adaptive cultivars in tidalswamplands, assessed the effect of land salinity to support rice Planting Index. The experiment wasconducted inTelangrejo tidal land, South Sumatra from February to November 2011. The study wasconducted with a split plot design with three replications. As Main plot were Amelioration and fertilization( M ) ; M1. Cultivation techniques used by farmers, M2. No-tillage ( TOT ) with inputs (lime wash + 3t / ha + fertilizer ), M3. Minimum tillage with input ( leaching + lime 3 t / ha + husk 3 t / ha + ZnSO4 +fertilizer ). Sub Plot were rice varieties (V); V1. Sintanur, V2. Inpara 1, V3. Inpara 2, V4. Inpara 4,V5. Inpara 5. Observations were made: 1 ) Plants growing, 2 ) grain yield and yield components.Multiple regression analysis showed that there were highly significant component effect on grain yield;the amount of total grain , the grain emptiness, and the weight of filled grains of 1000, where these threeoutcome components were also influenced by the treatment given of Amelioration. Some of varietieswere tested have different yields. The highest grain yield was Inpara 4 of 3.42 t / ha, followed by Inpara2 of 2.89 t/ha, while Inpari 1 showed a higher response for tidal land improvements, there weredifferences in responses between varieties. Although that was not statistically significant, the Ameliorationwas affect to the growth of rice, but the provision of husk and the addition of ZnSO4 were not affect tothe tidal rice in Tegalrejo.